Burden of Rota Virus Gastroenteritis in Children Under 5 Years of Age - Noor, Misbah; Ghani, Eijaz; Niazi, Saifullah Khan; Junaid, Muhammad; Khalid, Saadiya; Shakoor, Noman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To detect the burden of Rotavirus gastroenteritis in hospitalized and non-hospitalized children under 5 years of age. Study Design: Retrospective observational study. Place and Duration of Study: Department of Virology, Armed Forces Institute of Pathology, from Jan 2015 to Dec 2019. Methodology: A total of 527 stool samples were analyzed using rapid immunochromatoghraphic testing kit for Rotavirus. Samples were received from both outdoor and indoor children under 5 years of age presenting with diarrheal illness. Results: 197 (37.4%) patients were positive for rotavirus antigen in stool while 330 (62.6%) were negative. Mean age of participants was 13.4 months ± 16.6 (range: 1-60 months). Out of 197 (37.4%) stool samples which were positive for rotavirus antigen, 66 (33.5%) were female children and 131 (66.5%) were male children. Maximum positive rotavirus stool antigen was observed in 0-2 years age-group i.e., 173 (33%) while 24 (4.4%) were positive in 3-5 years age-group, 110 (20.9%) rotavirus positive samples were from Inpatient Department while 87 (16.5%) were received from Outpatient Department. Conclusion: Rotavirus is a frequent cause of viral gastroenteritis in both hospitalized and non-hospitalized children. Maximum positivity is seen in children under 2 years of age.